Protective Effects of Melatonin Against Zearalenone Toxicity on Porcine Embryos in vitro - Xu, Yao; Zhang, Kun-Huan; Sun, Ming-Hong; Lan, Mei; Wan, Xiang; Zhang, Yu; Sun, Shao-Chen (Frontiers in Pharmacology, 2019)
Zearalenone (ZEA) is an estrogenic mycotoxin produced by Fusarium fungi commonly found in corn, wheat and other cereals which can infect food and feed commodities, and ZEA mainly has reproductive toxicity which causes widely reproductive disorders in pigs and other animals. However, the toxicity and the functional ways of ZEA on early embryo development is still unclear. In present study we showed that exposure to ZEA (10μM) significantly decreased the 2-cell and blastocyst developmental rate in porcine early embryos in vitro. ZEA treatment resulted in the occurrence of oxidative stress, showing with increased reactive oxygen species (ROS) level, following with aberrant mitochondrial distribution. Moreover, we found positive signals of γH2A.X in the ZEA-treated embryos, indicating that ZEA induced DNA damage, and the increased autophagy confirmed this. These results suggested that ZEA induced oxidative stress, which further caused mitochondria dysfunction and DNA damage on early embryonic development. We next investigated the effects of melatonin on the ZEA-treated embryo development, and we found that melatonin supplementation could significantly ameliorate ZEA-induced oxidative stress, aberrant mitochondria distribution and DNA damage. In all, our results showed that ZEA was toxic for porcine embryos cultured in vitro and melatonin supplementation could protect their development from the effects of ZEA.